Health, Diet, and Violence during Wari Expansion: Bioarchaeology at Ak’awillay, Cusco, Peru - Bey, Bridget C.; Andrushko, Valerie A.; Bélisle, Véronique (Ñawpa Pacha, 2021)
The expansion of states and empires often has important consequences for local populations, including increased violence, greater stress, or dietary modifications resulting in changing health conditions. This paper presents the analysis of 73 skeletons from the Cusco site of Ak’awillay, shedding light on diet, health, and violence in the Middle Horizon. Results indicate that the people of Ak’awillay led a rigorous lifestyle and suffered from more nutritional deficiencies compared to previous populations, possibly pointing to increased maize consumption. However, the low incidence of trauma at Ak’awillay and other Cusco sites suggest that the Wari presence in Cusco was not entrenched in violence.
2 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/00776297.2021.1878602
Keywords: Horizonte Medio; Human remains; Middle Horizon; Wari; burials; dept.ant; diet; dieta; entierros; health; peer-reviewed; restos humanos; salud; violence; violencia